AWARENESS OF FEEDING HYDROPONIC MAIZE FODDER TO LIVESTOCK AMONG ELITES AND ITS EFFECT AS SUPPLEMENT ON EWES’ MILK - Muhammad, Ibrahim R.; Bashir, Fatima Abubakar; Shehu, Nawas U.; Ibrahim, Amrat M. (FUDMA JOURNAL OF SCIENCES, 2025)
A study was conducted to assess awareness of hydroponic maize fodder among elites and to evaluate its effect as a dietary supplement on milk production in lactating ewes. Awareness was determined using structured questionnaires administered to graduates within the university working with the university set up. For the feeding trial, twenty lactating ewes were assigned to four dietary treatments containing 0% (control), 10%, 20%, and 30% hydroponic maize fodder and fed at 3% of body weight for four weeks. Milk yield was measured by weighing lambs before and after suckling, and the chemical composition of the fodder was analyzed for crude protein, fibre, and energy content. Results showed that 85% of respondents practiced crop–livestock farming, 95% were aware of hydroponic maize fodder production, and 55% knew how to cultivate it. The hydroponic maize fodder contained 14.72% crude protein and 2593 kcal/kg metabolizable energy, meeting nutrient requirements for lactating sheep. Supplementation had a significant effect (p
Keywords: Hydroponics; Maize; Supplement; Livestock; Milk